Proses Produksi Isi Pemberitaan Isu Masa Kampanye Legislatif : Studi Kasus: Sebuah Harian di Jakarta - Sitinah, Sitinah; Maida, Serepina Tiur; Bachtiar, Alfan; Alamsyah, Alamsyah; Barizki, Rezzi Nanda (Prisani Cendekia Institute, 2024)
This research proves that the editorial policy of a mass media communication can be inserted by the personal interests of journalists or journalist crews, this happens because of the lack of supervision of journalist crews. The research is descriptive with qualitative data analysis, there are 5 sources, namely: Managing Editor, Editorial Policy Board, Editorial Secretary, Political Journalist and Public Relations Practitioner. The list of questions used is based on the results of the analysis of secondary research on monitoring the news of the legislative campaign period issues. From the analysis of news monitoring, it turned out that the news highlighted a particular political party. It was found that journalists used to insert information in their news without confirmation from media owners and managers.